Memories of Burmese Rohingya Refugees : Contested Identity and Belonging - Farzana, Kazi Fahmida (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book provides a critical analysis of the Rohingya refugees' identity building processes and how this is closely linked to the state-building process of Myanmar as well as issues of marginalization, statelessness, forced migration, exile life, and resistance of an ethnic minority. With a focus on the ethnic minority's life at the Myanmar-Bangladesh border, the author demonstrates how the state itself is involved in the construction of identity, which it manipulates for its own political purposes. The study is based on original research, largely drawn from fieldwork data. It presents an alternative and endogenous interpretation of the problem in contrast to the exogenous narrative espoused by state institutions, non-governmental organizations, and the media.
Keywords: Social sciences.; Ethnology -- Asia.; Social history.; Asia -- Politics and government.; Political sociology.; Emigration and immigration.; elektronické knihy; electronic books